The Students' Self-Confidence and Their Mathematical Communication Skills in Solving Problems - Retta Aulia; Rohati Rohati; Marlina Marlina (Edumatika, 2021)
This research aims to analyze students' mathematical communication skills in solving mathematical problems based on their self-confidence. This research was a qualitative research method with descriptive approach. This research was conducted at one of junior high school in Muaro Jambi, Jambi, Indonesia. The research subjects were six students consisting of two students with high self-confidence category, two students with medium category, and two students with low category who were selected using purposive sampling technique. This research used student self-confidence questionnaires, problem-solving tests, and interviews to confirm the level of students' mathematical communication skills. The data were analyzed by descriptive technique. The results showed that the subjects with high self-confidence had met all indicators of mathematical communication skills, while the subjects with medium self-confidence had met three of four indicators of mathematical communication skills, and the subjects with low self-confidence only fulfill one of four indicators of mathematical communication skills.